Cord blood therapy for pure red cell aplasia after allogeneic hematopoietic stem cell transplantation: case series and review - Li, Zhen; Zhuang, Sujing; Gui, Ruirui; Zhang, Binglei; Zhang, Wenli; Wang, Juan; Zu, Yingling; Yang, Fei; Xin, Xiangke; Liu, Yanyan; Zhang, Yanli; Fang, Baijun; et al. (Frontiers in Oncology, 2025)
IntroductionPure red cell aplasia (PRCA) is one of the complications after allogeneic hematopoietic stem cell transplantation (allo-HSCT). Its main pathogenesis is immune dysfunction leading to erythrocytes destruction. Currently, there is no gold standard for PRCA after allo-HSCT. Umbilical cord blood (UCB) and mesenchymal stem cells (MSCs) have been widely used in hematological and immune system diseases due to their hematopoietic reconstitution and immunomodulatory functions. However, few studies about using UCB and MSCs to treat PRCA after allo-HSCT have been reported.Case presentationIn this report, different cell therapy regimens of UCB and MSCs were used in 3 acute myeloid leukemia (AML) patients diagnosed with PRCA after allo-HSCT. Results showed that all patients achieved significant progress without adverse reactions or complications. Furthermore, Case 1 treated with UCB combined with umbilical cord MSCs (UC-MSCs), and Case 2 treated with 3 doses of UCB mononuclear cells (UCB-MNC) achieved earlier RBC transfusion independence (2 months and 2 weeks after cell therapy, respectively) than Case 3 treated with one unit of UCB (3 months after cell therapy).ConclusionThis report provides cell therapy strategies using UCB/UCB-MNC and UC-MSCs to treat PRCA after allo-HSCT. Our study demonstrates the safety and efficacy of 3 doses of UCB-MNC regimen and UCB combined with UC-MSCs regimen, providing a new treatment option for patients with PRCA after allo-HSCT.